Qur’an-Based Character Building (Akhlakul Karimah) Through A Daily Manners Habituation Program for Students Of TPQ Darul Iman Al Anshori Al Hasani - Nurul Laili; Ainur Rofiq Sofa (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2025)
This Community Service activity aims to implement and evaluate character development (akhlakul karimah) based on the Qur'an through a daily manners habituation program for TPQ Darul Iman Al Anshori Al Hasani students. The method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation involving the head of TPQ, managers, ustadz/ustadzah, and students. Data processing was carried out using a thematic analysis approach based on Braun and Clarke's model. The results of the activity show that before the program was implemented, students had a basic understanding of moral values, but had not applied them consistently. Character development is carried out through daily habits, examples from educators, and strengthening Qur'an values in various daily activities. This program has a positive impact on changing the attitudes and behaviors of students, such as increasing discipline, good manners, and a sense of responsibility. Although there are still obstacles related to consistency in habituation, this program has succeeded in improving Islamic character education in TPQ.